Pemberdayaan Guru Ekonomi MGMP melalui Literasi Kecerdasan Artifisial untuk Inovasi Pembelajaran - Della Fadhilatunisa; Rosidah; Sudarmanto Jayanegara; Muhalim; Dary Mochamad Rifqie (Jurusan Pendidikan Guru Sekolah Dasar Kampus VI Bone, 2025)
Digital transformation has brought artificial intelligence (AI) into various sectors, including education. In this context, teachers are expected not only to understand the teaching content but also to utilize technology in a critical and contextual manner. This community service activity was carried out in collaboration with Economics teachers who are members of the MGMP (Subject Teacher Forum) across South Sulawesi, aiming to explore the integration of AI in education. Using an Action Research (AR) approach, the program included basic AI concept training, prompt development workshops, and hands-on practice in creating AI-assisted teaching materials. The teachers actively engaged in designing learning content using tools such as ChatGPT, Notion AI, and Canva AI. Reflection and group discussions were integral parts of the collaborative learning process. The results show that the teachers were able to utilize AI technology in a contextual and creative way when developing instructional materials, and they demonstrated readiness to face the evolving landscape of educational technology.